Traceability and reputation in supply chains - Saak, Alexander E. (Elsevier, 2016)
The paper studies the questions of why and when a supply chain should invest in a traceability system that allows the identification of which supplier is responsible for quality defects due to insufficient non-contractible effort. We consider an environment with complementarity in upstream and downstream efforts to provide quality, imperfect, lagged signals of intermediate and final quality, and repeated interaction. It is demonstrated that in deciding whether to maintain information about product origin, firms face a trade-off. On one hand, the downstream firm is tempted to condone limited upstream shirking when products are not traceable to their firm of origin. On the other hand, the downstream firm is tempted to vertically coordinate shirking in the provision of quality when products are traceable. Perfect traceability is not optimal if (1) the ratio of the cost savings from upstream and downstream shirking is neither too high nor too low or (2) the downstream firm sufficiently infrequently detects input defects or (3) the consumer experience is a sufficiently noisy signal of quality.